Real‑world analysis of Macular Oedema associated with Paclitaxel Formulations using the Japanese Adverse Drug Event Report database - Koki Takeda; Toshinori Hirai; Ayu Sugioka; Rinka Okamura; Asako Nishimura; Nobuhito Shibata (PLoS ONE, 2026)
Aim This study explored the potential association between paclitaxel (PTX) and macular oedema (ME), a rare adverse event, through pharmacovigilance analysis using a large-scale spontaneous reporting database. Methods Disproportionality analysis of ME associated with PTX formulations, including nanoparticle albumin-bound PTX (nab‑PTX) was conducted using the Japanese Adverse Drug Event Report database on data collected during April 2004–June 2025. Multivariable logistic regression analysis was used to estimate adjusted reporting odds ratios (RORs) for ME. A positive signal was defined as a lower 95% confidence interval (CI) for the ROR exceeding 1.0 with at least three ME cases. Results Among 585,738 reports, 123 involved ME. A significant signal was observed for overall PTX (adjusted ROR: 19.5; 95% CI: 13.5–28.3). By formulation, significant signals were identified for conventional PTX (adjusted ROR: 9.4; 95% CI: 5.5–16.1) and nab‑PTX (adjusted ROR: 47.0; 95% CI: 30.4–72.8). Multivariable logistic regression indicated significant signals for diabetes mellitus (adjusted ROR: 1.8; 95% CI: 1.2–2.9) and co-administration of prostaglandin analogue eye drops (adjusted ROR: 19.9; 95% CI: 8.6–45.7). Conclusion PTX formulations were associated with an increased reporting signal of ME. Notably, patients with diabetes mellitus and those using prostaglandin analogue eye drops may require closer ophthalmologic monitoring during PTX therapy.